Dyadic social interaction inhibits cocaine-conditioned place preference and the associated activation of the accumbens corridor - Zernig, Gerald (Behav Pharmacol, 2015)
Impaired social interaction is a hallmark symptom of many psychiatric disorders. In substance use disorders, impaired social interaction is triply harmful (a) because addicts increasingly prefer the drug of abuse to the natural reward of drug-free social interaction, thus worsening the progression of the disease by increasing their drug consumption, (b) because treatment adherence and, consequently, treatment success itself depends on the ability of the recovering addict to maintain social interaction and adhere to treatment, and (c) because socially interacting with an individual suffering from a substance use disorder may be harmful for others. Helping the addict reorient his/her behavior away from the drug of abuse toward social interaction would therefore be of considerable therapeutic benefit. This article reviews our work on the neural basis of such a reorientation from cocaine, as a prototypical drug of abuse, toward dyadic (i.e. one-to-one) social interaction and compares our findings with the effects of other potentially beneficial interventions, that is, environmental enrichment or paired housing, on the activation of the accumbens and other brain regions involved in behavior motivated by drugs of abuse or nondrug stimuli. Our experimental models are based on the conditioned place preference paradigm. As the therapeutically most promising finding, only four 15 min episodes of dyadic social interaction were able to inhibit both the subsequent reacquisition/re-expression of preference for cocaine and the neural activation associated with this behavior, that is, an increase in the expression of the immediate early gene Early Growth Response protein 1 (EGR1, Zif268) in the nucleus accumbens, basolateral and central amygdala, and the ventral tegmental area. The time spent in the cocaine-associated conditioning compartment was correlated with the density of EGR1-activated neurons not only in the medial core (AcbCm) and medial shell (AcbShm) of the nucleus accumbens, but was observed in all regions medial to the anterior commissure (‘accumbens corridor’), including (from medial to lateral), the vertical limb of the diagonal band and the medial septum (VDB+MS), the major island of Calleja and the intermediate nucleus of the lateral septum (ICjM+LSI), the AcbShm, and the AcbCm. All effects were limited to GABAergic projection neurons (called ‘medium spiny neurons’, in the accumbens), encompassing both dopamine D1 receptor-expressing and D2 receptor-expressing medium spiny neuron subtypes. Our EGR1 expression findings were mirrored in multielectrode array recordings. Finally, we have validated our paradigm in C57BL/6 mice to make use of the plethora of transgenic models available in this genus.